2018
DOI: 10.21037/atm.2017.09.29
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following transcatheter aortic valve replacement in patients with native aortic valve regurgitation

Abstract: Due to the absence of annular calcification for device anchoring, it is presumed that transcatheter aortic valve replacement (TAVR) is not suitable for the treatment of native aortic valve regurgitation (NAVR) resulting in very limited data and experience concerning its safety and efficacy. We sought to review published data on the safety and efficacy of TAVR in high-risk patients with NAVR. Studies including case reports, case series and original articles published between 2002 and 2016 on TAVR in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Three patients with Venus-A valves and 6 patients with VitaFlow valves required new permanent pacemaker placement after TAVR. The new permanent pacemaker placement rate in our study was similar to that reported in previous studies of pure AR (7,10,19,20). The two domestic valves used in this study were both first-generation devices, which were recommended to be released at a lower position because of their non-recapturable systems in patients with AR, thus being associated with a high risk of new permanent pacemaker placement.…”
Section: Discussionsupporting
confidence: 87%
“…Three patients with Venus-A valves and 6 patients with VitaFlow valves required new permanent pacemaker placement after TAVR. The new permanent pacemaker placement rate in our study was similar to that reported in previous studies of pure AR (7,10,19,20). The two domestic valves used in this study were both first-generation devices, which were recommended to be released at a lower position because of their non-recapturable systems in patients with AR, thus being associated with a high risk of new permanent pacemaker placement.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the systematic reviews covering the area of AV repair, evidence remains heterogenous and registries are underway to try and pool and analyse cohorts of patients undergoing AV repair. (27)Percutaneous intervention -TAVIAR is traditionally a contraindication to TAVI as the calcified landing zone is often lacking,(34) removing anatomical landmarks for alignment and potentially leading to malposition (35). Furthermore, increased movement of valve prosthesis in the regurgitant jet as well as aortic root dilatation may lead to suboptimal prosthesis position and paravalvular leak necessitating a second valve-in-valve prosthesis.…”
mentioning
confidence: 99%
“…In fact, there remains a long way before we reach the moon: combining TEVAR and transcatheter aortic valve intervention in a smooth and non-calcified aortic valve. 11 We need not only courage but also innovation and new dedicated devices. 12…”
mentioning
confidence: 99%